Application of Conceptions of Non-profit Marketing in Professional Training of the Unemployed - Šmergelienė, Valdonė (Ekonomika, 2004)
This article deals with the usage of elements of marketing in the services of professional training of unemployed people. The majority of organisations that work in professional training belong to the non-profit sector. The usage of marketing concepts in these circumstances is highly specific and has to address the characteristics of both public and non-profit sectors. Quite often the main problem is the lack of a really systematic approach in attempting to understand the effects of nonprofit I social marketing. In the sphere of professional training of the unemployed, it is important to use marketing elements at all levels: at a state level, regional level, institutional level and even at an individual client level. All organizations acting in this sphere can apply the concepts of marketing, i.e. those of non-profit marketing, marketing of labour market, marketing of education, and social marketing.